Resiliensi Mahasiswa Bidikmisi Tingkat Pertama Universitas Padjadjaran - Fadila Hediaty Zahra; Hutami Rachmat Nabilah; Miryam Wedyaswari (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
he resilience process is dynamic, including protective factors, risk factors, and resilient outcomes. The first-year bidikmisi students of Padjadjaran University are considered to have more risk than other students because they have disadvantages in the economic field, adapt to the new environment, and demand immediate education before economics assistance is revoked. Seven critical factors that can support resilience. This study aims to determine the resilience condition of first-year bidikmisi students of Padjadjaran University as data for subsequent policymaking and develop the Reivich-Shatte resilience theory to contribute to the development of science. The research method is the descriptive approach with quantitative data types and 178 sample students (65,7% female). The results showed that most students are at the upper average level on three factors, control, empathy, and connecting & reaching out. Students' perceptions of these factors are adequate, and they need to be accustomed to using them in everyday life so their abilities can be classified as high. Meanwhile, most students are at the lower average for emotional regulation, realistic optimism, causal analysis, and self-efficacy.